2015
DOI: 10.2196/jmir.4364
|View full text |Cite
|
Sign up to set email alerts
|

More Than Telemonitoring: Health Provider Use and Nonuse of Life-Log Data in Irritable Bowel Syndrome and Weight Management

Abstract: BackgroundThe quantified self, self-monitoring or life-logging movement is a trend to incorporate technology into data acquisition on aspects of a person's daily life in terms of inputs (eg food consumed), states (eg mood), and performance (mental and physical). Consumer self-monitoring mobile phone apps have been widely studied and used to promote healthy behavior changes. Data collected through life-logging apps also have the potential to support clinical care.ObjectiveWe sought to develop an in-depth unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
160
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(167 citation statements)
references
References 43 publications
6
160
0
1
Order By: Relevance
“…Past literature has suggested patient generated health data may lead to better communication between the patient and provider, help set goals, and discover patient habits and preferences [26]. Additionally, some studies have shown that when patients bring information to their visits better health outcomes were achieved [24,34,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Past literature has suggested patient generated health data may lead to better communication between the patient and provider, help set goals, and discover patient habits and preferences [26]. Additionally, some studies have shown that when patients bring information to their visits better health outcomes were achieved [24,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The survey was developed through a literature review of provider perceptions regarding various technologies and patients bringing information to the visits [24,32]. The survey included 25 questions total pertaining to providers' use of these technologies (as defined above, the consumer-grade sensor devices (e.g., Fitbit) and Web/smartphone-based applications (e.g., MyFitnessPal) (apps)), their patients' use of these technologies, their perceptions on the usefulness of these technologies, and demographic questions.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…While patients may wish to share this type of data with their clinical providers, there are few tools that help providers access, integrate, and review the large volumes of data that can be collected through mobile devices (Chung, Cook, Bales, Zia, & Munson, 2015; Torous & Baker, 2016). Additional research is needed to identify methods for efficiently extracting actionable information from mobile data with minimal effort on behalf of providers, and to understand the extent to which this data impacts clinical decision-making and depression outcomes.…”
Section: Measurement-based Carementioning
confidence: 99%
“…For example, Lee and Dey’s embedded assessment tool provides patients with a way to effortlessly supply data to clinicians about their ability to perform everyday tasks [24]. Chung et al examine how providers use patient-generated life-logging data in their practice [9]. …”
Section: Related Workmentioning
confidence: 99%